Charge-Transfer Complex between 3,5-Diamino-1,2,4-Triazole and 6-Methyl-1,3,5-Triazine-2,4-Diamine with Chloranilic Acid: Thermodynamic Study and Spectroscopic Analysis - Al-Ahmary , Khairia M.; Alharbi , Ashwaq T. (Recent Developments in Chemistry and Biochemistry Research Vol. 1, 2024)
Studying of charge-transfer (CT) and proton transfer interactions is essential due to their important role in many biological field and industrial applications. Triazine compounds are well known due to their broad biological activity towards several diseases such as analgesic, anti-inflammatory, anti-oxidant, analeptic. The current work will add more information’s about the nature of interaction between 3,5-diamino-1,2,4-triazole (DAT) and 6-methyl-1,3,5-triazine-2,4-diamine (MTDA) with 3,6-dichloro-2,5-dihydroxy-p-benzoquinone (chloranilic acid CLA) which was studied spectrophotometrically in Ethanol (EtOH) and Methanol (MeOH) solvents at different temperatures. Based on the formation of stable purple colored CT-complex between CLA and donors, we proposed a simple, rapid, and accurate spectrophotometric method for determination of donors. The molecular composition of the formed complexes was studied by applying continuous variation and spectrophotometric titration methods and found to be 1:1 charge transfer complex for both Complex (DAT:CLA) and (MTDA:CLA) which are produced. Minimum-Maximum absorbance’s method has been applied to calculate the formation constant KCT and molecular extinction coefficient (\(ε\) ); they recorded high values confirming high stability of the produced complexes. Oscillator strength (f), transition dipole moment ( \(μ\) ), ionization potential (IP) and dissociation energy (W) of the formed CT-complexes were also determined and evaluated; they showed solvent dependency. The accuracy and precision of the method was established by performing analysis of solutions containing five different amounts (within Beer’s law limits) of all donors and measuring the absorbance of their HBCT complexes with CLA in EtOH and MeOH. It is concluded that the formation constant (KCT) of the complexes is found to depend on the nature of both electron acceptor and donors and on the polarity of solvents.